Some Misconceptions about Public Investment Efficiency and Growth - Berg, Andrew (IMF Working Papers; Working Paper ;, 2015)
We reconsider the macroeconomic implications of public investment efficiency, defined as the ratio between the actual increment to public capital and the amount spent. We show that, in a simple and standard model, increases in public investment spending in inefficient countries do not have a lower impact on growth than in efficient countries, a result confirmed in a simple cross-country regression. This apparently counter-intuitive result, which contrasts with Pritchett (2000) and recent policy analyses, follows directly from the standard assumption that the marginal product of public capital declines with the capital/output ratio. The implication is that efficiency and scarcity of public capital are likely to be inversely related across countries. It follows that both efficiency and the rate of return need to be considered together in assessing the impact of increases in investment, and blanket recommendations against increased public investment spending in inefficient countries need to be reconsidered. Changes in efficiency, in contrast, have direct and potentially powerful impacts on growth: 'investing in investing' through structural reforms that increase efficiency, for example, can have very high rates of return.